Elucidation of clinical, environmental and T helper 2 factors on tight junction expressions in allergic rhinitis - Muhamad, Siti Nur Husna (2022)
The breakdown of nasal epithelial barrier via the impairment of cell junction components including tight junctions (TJs) and desmosomes plays causative roles in the pathogenesis of allergic rhinitis (AR). However, the associations between nasal epithelial TJs and desmosomes expression with demographical, clinical and environmental characteristics, as well as with T helper 2 (Th2) cytokines and Th2 cytokine receptors remain unclear. Therefore, this study aimed to investigate these in a cohort of AR patients vs non-allergic controls. Thirty house dust mite (HDM)-induced moderate/severe AR patients and 30 non-allergic controls were recruited in this study, and HDM sensitisations were assessed through skin prick test (SPT). mRNA expression levels of TJ genes (OCLN, CLDN3 and CLDN7), desmosomes (DSG1 and DSG3), TSLP (an epithelium-derived cytokine) and Th2 cytokine receptors (IL4R, IL5RA, IL6R and IL13RA1) in nasal epithelial cells of AR patients vs non-allergic controls were investigated via quantitative reverse transcription polymerase chain reaction (RTqPCR). Serum levels of Th2 cytokines (IL-4, IL-5, IL-6 and IL-13) of AR patients vs non-allergic controls were investigated using Magnetic Luminex® Assay and the correlations between IL-4/IL-13 receptor heterodimer with TJ genes expressions were determined via bioinformatics analysis. It was observed, for the first time, that SPT wheal sizes of D. farinae sensitisation were significantly associated with higher severity scores of nasal and non-nasal symptoms, and these associations were not observed in SPT wheal sizes of D. pteronyssinus and B. tropicalis sensitisation. In terms of TJs, the expression levels of OCLN, CLDN3 or CLDN7 (but not DSG1, DSG3 or TSLP) transcripts were significantly lower in AR patients compared with non-allergic controls. A significant association between urban locations and lower OCLN expression, or exposure to second-hand smoke with lower CLDN7 expression was found in AR patients. Next, the roles of IL-4/IL-13 axis in AR were observed where significantly higher levels of serum IL-4, IL-5, IL-6 and IL-13, and increased IL13RA1 expression were found in AR patients compared to non-allergic controls. Serum IL-4 and IL-13 levels were positively correlated with IL13RA1 expression in AR patients but not in non-allergic controls. Essentially, correlation analyses of a gene expression profiling dataset (GSE44037; 12 AR patients vs six non-allergic controls) showed that six TJ (CLDN4, CLDN7, CLDN12, CLDN15, TJP1 and TJP2) and two JAK/STAT signaling (STAT2 and STAT3) genes expressions were positively and negatively correlated, respectively, with IL-4Rα/IL-13Rα1 heterodimeric receptor expression in AR patients. These were not observed in non-allergic control samples. Lastly, STATs DNA binding motif analysis showed that each of these six TJ genes contains STATs binding consensus sequence within their DNA regulatory regions. Collectively, these suggest that the IL-4/IL-13 axis signalling via the JAK/STAT pathway represses the expression of TJs in AR patients. In conclusion, targeting nasal epithelial through restoring the expression of TJs as well as targeting IL-4/IL-13 axis and its downstream JAK/STAT pathway may represent a novel approach in developing targeted therapies for AR patients.